Clonal hematopoiesis associated with epigenetic aging and clinical outcomes. Issue 6 (29th May 2021) - Nachun, Daniel; Lu, Ake T.; Bick, Alexander G.; Natarajan, Pradeep; Weinstock, Joshua; Szeto, Mindy D.; Kathiresan, Sekar; Abecasis, Goncalo; Taylor, Kent D.; Guo, Xiuqing; Tracy, Russ; Durda, Peter; et al.
Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) is a common precursor state for blood cancers that most frequently occurs due to mutations in the DNA‐methylation modifying enzymes DNMT3A or TET2 . We used DNA‐methylation array and whole‐genome sequencing data from four cohorts together comprising 5522 persons to study the association between CHIP, epigenetic clocks, and health outcomes. CHIP was strongly associated with epigenetic age acceleration, defined as the residual after regressing epigenetic clock age on chronological age, in several clocks, ranging from 1.31 years (GrimAge, p < 8.6 × 10 −7 ) to 3.08 years (EEAA, p < 3.7 × 10 −18 ). Mutations in most CHIP genes except DNA‐damage response genes were associated with increases in several measures of age acceleration. CHIP carriers with mutations in multiple genes had the largest increases in age acceleration and decrease in estimated telomere length. Finally, we found that 40% of CHIP carriers had acceleration >0 in both Hannum and GrimAge (referred to as AgeAccelHG+). This group was at high risk of all‐cause mortality (hazard ratio 2.90, p < 4.1 × 10 −8 ) and coronary heart disease (CHD) (hazard ratio 3.24, p < 9.3 × 10 −6 ) compared to those who were CHIP−/AgeAccelHG−. In contrast, the other 60% of CHIP carriers who were AgeAccelHG− were not at increased risk of these outcomes. In summary, CHIP is strongly linked to age acceleration in multiple clocks, and the combination of CHIP and epigenetic aging may be used to identify a population at high risk for adverse outcomes and who may be a target for clinical interventions. Abstract : Clonal hematopoiesis of indeterminate potential (CHIP) and epigenetic age acceleration are the two important aging phenomenon associated with adverse clinical outcomes. We found that mutations in most CHIP genes were associated with increased age acceleration in multiple epigenetic clocks. Individuals with CHIP and age acceleration had a greatly increased risk of mortality and coronary heart disease compared to individuals with only CHIP or age acceleration.